Propuesta de un Manual de Buenas Prácticas de Manufactura (BPM) en el proceso de fabricación en la empresa “Como Arroz” (2021)
This work was carried out in the restaurant "Como Arroz", located in the city of Villavicencio - Meta, with the objective of proposing a manual of Good Manufacturing Practices (GMP) in the food manufacturing process, based on decree 3075 of 1997, which establishes the general provisions that regulate all activities that can create risk factors for food consumption. Initially, a documentation of the processes carried out in the restaurant "Como Arroz" was made, which are: storage process, elaboration process and packaging process. Subsequently, a diagnosis was made to identify compliance with good manufacturing practices (GMP) in the food manufacturing process in the company, by means of checklists. The restaurant presented 57%, 66% and 64% compliance and 43%, 34% and 36% non-compliance in the storage, processing, and packaging processes, respectively.